Амнезия души: [роман] / Татьяна Коган - Коган Татьяна Васильевна (Чужие игры, 2015)
Экземпляры: СБ (20160520) / Инвентарный номер: 52217 / Цена: 140.00 / Сис.шифр: Р2 / Авт.знак: К 57 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6